Boosting algebra mastery through activity-based learning in an indigenous peoples education secondary school - Apdo, Rolly Najial; Apdo, Rachel Basañez (Institute of Advanced Engineering and Science, 2025)
Algebra is a fundamental area of mathematics, yet many students, particularly indigenous learners, struggle with its concepts and procedures. This study examines the impact of activity-based learning on the conceptual understanding and procedural skills of junior high school students in an indigenous peoples education (IPEd) school. Using a mixed-methods approach, 105 indigenous students from grades 7 to 9 at Daan Taligaman Integrated Secondary School (DTISS), Philippines, participated. Pre-test and post-test scores were analyzed using a paired-samples t-test, while thematic analysis explored students’ learning experiences. The results revealed significant improvements in both conceptual understanding and procedural skills, with grade 7 scores increasing from 41.08% to 80.38% (conceptual) and 34.83% to 74.13% (procedural). A similar trend was apparent for the grades 8 and 9 students. Key themes identified were engagement and enjoyment, increased confidence, and improved understanding. The study highlights the effectiveness of interactive, culturally responsive learning strategies in enhancing algebra mastery among indigenous students and calls for their integration into mathematics education.